2016
DOI: 10.12681/scad.8975
|View full text |Cite
|
Sign up to set email alerts
|

Employment request in the healthcare sector: A case of a specialized not-for-profit hospital in Greece

Abstract: <p>This paper presents the findings of a novel<br />research conducted in a specialized, not-forprofit<br />hospital in Greece. The authors analysed<br />775 curriculum vitae (CVs) that were<br />spontaneously submitted to the healthcare<br />organisation in a two-year period and did<br />not refer to a specific job opening. The research<br />is novel, as it was performed in a not-forprofit hospital under the supervision of<br />the Ministry of Health and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Relationships among staff based on cordiality, teamwork, recognition and collaboration would have a positive impact on HC performance. This finding is consistent with recent studies on the impact of human resources satisfaction in the healthcare sector (Souliotis et al , 2014). This dimension also reflects the relationships among the professionals and with the patient and their families.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Relationships among staff based on cordiality, teamwork, recognition and collaboration would have a positive impact on HC performance. This finding is consistent with recent studies on the impact of human resources satisfaction in the healthcare sector (Souliotis et al , 2014). This dimension also reflects the relationships among the professionals and with the patient and their families.…”
Section: Discussionsupporting
confidence: 94%
“…Healthcare organizations also have some unique human resources-related characteristics. Souliotis et al (2014) refer to healthcare organizations as social systems where human resources are the most important factors affecting the quality of care, and effectiveness and efficiency of the organization. The organization’s orientation and operations are strongly influenced by the activities of the professional groups, who are those uniquely qualified to determine how the operations should be carried out (Sicotte et al , 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to [ 21 , 22 , 23 ], human resources are even more important in the medical field because almost all employees contact the beneficiaries of health services regardless of their positions. However, the literature [ 10 , 18 , 19 , 20 ] has shown that although most hospitals recognize the worth of employees at the basic service level (in direct contact with the patient), some healthcare organizations do not understand the factors that motivate these employees.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Certainly, GHCS is not the only case: the 2001, Institute Of Medicine report asserted that the safety and quality problems of United States health care system exist because of limited infrastructure and outmoded systems unable to incorporate the improvement measures, which result in a cycle of suboptimal care being repeated throughout the many levels of care [18,21].…”
Section: The Need For Disease Management In Greecementioning
confidence: 99%